Identifying and Prioritizing Creative Tourism Attractions in the Life of the Nomads from the Guest-Host Perspective (Case study: Bakhtiari Tribe, Khuzestan Province) - Mehrnoosh bastenega; Anahita Azarbod (گردشگری و اوقات فراغت)
This study aims to identify and prioritize creative tourism attractions in nomadic life from a host-guest perspective. The research method is descriptive-analytical and the statistical population includes tour guides and nomadic tourism activists. The study data was collected based on the decision matrix pattern, which includes options and indicators, based on the subjective judgments of a 15-person sample of the statistical population selected by the snowball method. The data obtained from the combination of the opinions of the sample members were analyzed using the Shannon entropy technique for evaluating the indicators and TOPSIS for prioritizing the attractions from the host and guest perspectives. The findings show that from the host's perspective, the demand indicators, Attracting tourists, contribution to the local economy, diversity, and tourist participation impact the ranking of tourist attractions, respectively. From the guest's perspective, the indicators of influence on the tourist experience, uniqueness, connection with history and culture, diversity, and opportunity for cultural improvement are, respectively, influential in the ranking of tourist attractions. The results also indicate that from the host's perspective, handicrafts, food and cuisine, music, customs, Migration architecture, and literature are the most important creative tourism attractions in nomadic life, respectively. From the guest's perspective, handicrafts, music, food and cuisine, Migration architecture, customs, and literature are the most important creative tourism attractions in nomadic life, respectively. These results can bring the views of the supply and demand sides closer together and provide an effective basis for formulating creative tourism development strategies in nomadic.